Ecological Approach in the Substantiation of the Contexts of Distance Education Environment - Katane, Irēna; Katans, Edgars; Vavere, Gita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The development of a human being takes place in the interaction with his/her life environment. Educational environment, including distance education environment, is particularly important for the facilitation of the sustainability of all society and the development of each individual. Ecological paradigm becomes more and more topical in modern education. The authors of the article base their research on the ecological approach, where an educational institution as the distance education environment is a multicomponent/multicontextual system. The results of theoretical research enabled the authors to identify several contexts of distance education environment: informative environment, technological environment and e-environment that complementary supplement each other. There have been analyzed and compared several concepts related to distance education, identifying in them the common and different features. Ecological approach enabled to reveal the essence of distance education and to describe distance education environment from different aspects.